FRACTURE SEALING IN ZIRCON AS EVALUATED BY ELECTRON MICROPROBE ANALYSES AND BACK-SCATTERED ELECTRON IMAGING - Hartmann L.A.; Takehara L.; Leite J.A.D.; McNaughton N.J.; Vasconcellos M.A.Z. (My University, 1997)
The internal structure of zircon is commonly revealed by back-scattered electron (BSE) images. Grains from a 750-700 Ma old calc-alkaline mafic metatonalite from southernmost Brazil show relict igneous faces, irregular and diffuse metamorphic overgrowths, and fracture sealing. Sealing of fractures is observed as light grey patches in BSE images. EPMA profiles show strong but differential increases in Hf and U in the sealed fractures, unlike the common assertion in the literature that fractures are only pathways of leaching. Sealing of fractures occurs near borders of grains as well as in their cores and is not visible during standard petrographic examination; thus careful BSE image evaluation is needed before either in situ or whole grain isotopic determinations are made.
Keywords: ZIRCON; FRACTURE; METASOMATISM; GEOCHEMISTRY; TRACE ELEMENTS; CATHODOLUMINESCENCE; BACKSCATTERED ELECTRON IMAGING